Ratapan Umat di Tengah Krisis Ekonomi dan Politik: Tafsir Mazmur 80 - Elifas Tomix Maspaitella (Program Pascasarjana UKIM, 2022)
This article aims to interpret Psalm 80 and explore its implications. Restoring power is derived from the original national spirituality. Every nation, in any civilization, has national spirituality that was born from the noble promise when the nation was formed. The noble commitment is a manifestation of the work and role of the Holy Spirit, who gave wisdom to the nation's founders with one goal: to build a country that unites its pluralistic people and fights for prosperity, justice, truth, and integrity for its pluralistic people equally. With a socio-exegetic approach, the author asserts that the practice of restoring power is a manifestation of God's authority in the nation.